A Compensator Microelectromechanical Acceleration Transducer with a Piezoelectric Sensing Element and Optical Reading - V. I. Busurin; K. A. Korobkov; Lwin Htoo Zaw (Известия высших учебных заведений России: Радиоэлектроника, 2024)
Introduction. Modern mobile control objects require the use of highly sensitive transducers of motion parameters, e.g., acceleration, with a wide measurement range. Increased sensitivity to measured parameters can be achieved by using precision optics, e.g., based on the tunneling effect. However, operating ranges of induced movements are less than a micrometer, which creates difficulties in positioning the sensing element. In order to improve manufacturability, to extend the measurement range and to reduce errors of acceleration transducers with optical tunneling, compensation circuits with a piezoelectric actuator as an active sensor can be used.Aim. To extend the measurement range of microelectromechanical acceleration transducers through the use of an integrated approach, including the introduction of a compensation circuit for sensor movements based on the inverse piezoelectric effect and detection of these movements by optical means.Materials and methods. An approach to compensating sensor movements is proposed. This approach consists in using a bimorph piezoelectric plate as an inertial element. The use of optical reading of sensor sub-micrometer displacements is considered.Results. A block scheme and a functional scheme of a compensator micro-opto-electromechanical acceleration transducer with a bimorph piezoelectric sensing element are developed. Deformations in the sensing element under the influence of accelerations (up to 100 m/s2) and compensation voltages, whose amplitude does not exceed several volts, are investigated to ensure the possibility of using the optical tunneling effect in the proposed transducer.Conclusion. A mathematical model of the transducer was developed and studied. A 2.5-fold increase in the  measurement range was achieved. It was shown that the introduction of compensation feedback does not decrease the permissible frequency range of measured accelerations.